2019
DOI: 10.1063/1.5093698
|View full text |Cite
|
Sign up to set email alerts
|

Development of a compact laser-diode based frequency domain photoacoustic sensing system: Application of human breast cancer diagnosis

Abstract: We present the development of a laser diode based photoacoustic spectral response (PASR) setup capable of diagnosing human breast cancer tissues through the use of mechanobiological properties of the tissue. A detailed description of the laser driver is provided, highlighting the important characteristics of the developed driver. Furthermore, the amplifier development is described. The developed laser diode based PASR system has been characterized using standard samples. Subsequently, the developed experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The PA time domain signal was obtained from biopsy excised breast tissue in continuous mode. Further spectral energy was calculated from PA frequency spectra of normal and malignant tissues, which illustrated that malignant tissues elucidate higher spectral energy compared to normal tissues [126]. Choi et al reported wavelength modulated differential photoacoustic spectroscopy (WM-DPAS) for early-stage cancer diagnosis through change in total hemoglobin concentration and oxygenation levels (StO 2 ).…”
Section: Cancer Diagnosismentioning
confidence: 99%
“…The PA time domain signal was obtained from biopsy excised breast tissue in continuous mode. Further spectral energy was calculated from PA frequency spectra of normal and malignant tissues, which illustrated that malignant tissues elucidate higher spectral energy compared to normal tissues [126]. Choi et al reported wavelength modulated differential photoacoustic spectroscopy (WM-DPAS) for early-stage cancer diagnosis through change in total hemoglobin concentration and oxygenation levels (StO 2 ).…”
Section: Cancer Diagnosismentioning
confidence: 99%
“…(17). 15 20 For the specialized LED/LD module having a very high repetition rate, like a few hundred KHz, the becomes very low, like a few ten-thousandth, 21 which makes increased up to a few tens of MHz. Therefore, it is reasonable to consider that achieving the maximum repetition rate or, equivalently, the maximum pulse number is almost impossible for almost all practical LED/LD-based PA systems.…”
Section: Snr Ratio For Pulse Train and Chirp Waveformsmentioning
confidence: 99%
“…However, due to existing conventional thought that pulse PA signals exhibit higher SNRs than continuous ones, the majority of LED/LD-based PA imaging studies have been conducted with pulse-mode or pulse LDs. 14 , 16 18 The usage of pulse LDs limits the development of PA spectroscopic imaging systems because the typical wavelength of most commercially available pulse LDs is in the range of near-infrared more than . 15 , 17 , 18 Additionally, most pulse LDs operate with a very low power per pulse, which could lead to the reduction of overall fluence and real-time PA measurement capability.…”
Section: Introductionmentioning
confidence: 99%